A preliminary investigation on the distribution of cannabinoids in man - Gronewold, Antonia; Skopp, Gisela (Forensic science international, 2011)
An LC/MS/MS procedure to determine THC along with its major metabolites 11-OH-THC, THC-COOH and its glucuronide as well as the cannabinoids CBD and CBN was applied to 5 post mortem cases to study their distribution into some less commonly studied matrices. Analytes were determined in fluids and tissue homogenates following protein precipitation and liquid-liquid extraction. Gall bladder fluid exhibited maximum concentrations of all analytes except THC, which was detectable in high concentrations in muscle tissue along with CBD. THC was also present in lung specimens, whereas its concentration in liver samples was low or not detectable at all. Liver und kidney specimens contained appreciable amounts of THC-COOglu. Findings from bile support extensive enterohepatic recirculation of the glucuronide. Muscle tissue seems an interesting specimen to detect multiple cannabis use, and brain may serve as an alternative specimen for blood; nevertheless, the present findings should be substantiated by further investigations.